FAKTOR FAKTOR YANG MEMPENGARUHI LAYANAN RESERVASI HOTEL DI PT. BALI MEGAH WISATA TOUR AND TRAVEL - Bramantya Agustiano, Si Gede Ngurah; Kusuma Negara, I Made; Suardana, I Wayan (Jurnal IPTA (Industri Perjalanan Wisata); Vol 4 No 1 (2016): Jurnal IPTA (July 2016)DO - 10.24843/IPTA.2016.v04.i01.p16, 2016)
This study aims to determine the factors that influence hotel reservation service at Bali Megah Wisata Tour and Travel and a contributing factor dominant in hotel reservation service at Bali Megah Wisata Tour and Travel. The respondents in this study use purposive sampling technique in which the criteria are tourists who have made hotel reservation at Bali Megah Wisata Tour and Travel, with the total sample of 190 respondents. Questionnaires were used to collect data have been tested for validity and reliability. The data analysis which is used to answer the hypothesis of this study is factor analysis. The results of factor analysis showed that 5 factors affecting hotel reservation service at Bali Megah Wisata Tour and Travel are structur and ease of use factor with eigen value 6,492, reputation and security factor with eigen value 2,671, usefulness factor with eigen value 2,497, information content factor with eigen value 1,889 and responsiveness and personalization factor with eigen value 1,059. Structure and ease of use factor is a contributing factor dominant in hotel reservation service at Bali Megah Wisata Tour and Travel.
Keywords: Quality Service, Hotel Reservation